Conceptual model of Excavation and Transport vehicle at Shakelton Crater - ivan rojas (2021)
The moon is filled with a plethora of materials in order to provide sustained research and development. In order to realize such methods, there exist historical approaches, by both NASA, the excavation sector, ice core research facilities, and even the agricultural space to help guide the development of mechanisms appropriate for lunar excursions. This project aims to address challenges concerning the extraction of regolith and hypothesized ice below the surface of the moon for the processing and transport of water on the lunar surface by implementing an excavation design derived by known techniques utilized in similar environments found here on earth.